2012
DOI: 10.1590/s1516-35982012001100007
|View full text |Cite
|
Sign up to set email alerts
|

Growth, carcass characteristics, chemical composition and fatty acid profile of the longissimus dorsi muscle in goat kids fed diets with castor oil

Abstract: The objective in this study was to determine growth, carcass characteristics, chemical composition and fatty acid profile of the longissimus dorsi of crossbred Boer × Saanen kids fed castor oil. Twenty-four kids (12 males and 12 females) were assigned in a randomized complete block design with two treatments and twelve replications. Blocks were defined according to weight, gender and initial age of animals for the evaluation of performance. The experimental treatments consisted of two diets containing 900 g co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…The oil blend used in the current study had no effect on the in vitro (Adeyemi et al 2015a) and in vivo (Adeyemi et al 2015c) ruminal concentration of propionate and this could be responsible for the similarity in the intramuscular fat across the treatments. The current finding is similar to the insignificant deposition of intramuscular fat observed when castor oil (Maia et al 2012) and sunflower oil (Marinova et al 2001) were supplemented in goats' diets.…”
Section: Levels Of Oil Blend (%)supporting
confidence: 86%
“…The oil blend used in the current study had no effect on the in vitro (Adeyemi et al 2015a) and in vivo (Adeyemi et al 2015c) ruminal concentration of propionate and this could be responsible for the similarity in the intramuscular fat across the treatments. The current finding is similar to the insignificant deposition of intramuscular fat observed when castor oil (Maia et al 2012) and sunflower oil (Marinova et al 2001) were supplemented in goats' diets.…”
Section: Levels Of Oil Blend (%)supporting
confidence: 86%
“…Ricinoleic acid is known to have antimicrobial properties (Novak et al, 1961); thus, it has been studied as a possible modulator of ruminal fermentation to be used as an alternative to ionophore additives to improve growth, feed intake, and efficiency. Indeed, inclusion of castor oil in diet of dairy cows (Gandra et al, 2014;de Jesus et al, 2016), bulls (Cruz et al, 2014;Silva et al, 2014), steers (Gandra et al, 2012), sheep (Maia et al, 2012a), or goat kids (Maia et al, 2012b) did not impair nutrient intake, digestibility, or growth performance.…”
Section: Introductionmentioning
confidence: 94%
“…However, in both studies the FA profile was limited and none of these studies identified the ricinoleic acid or other hydroxy-FA derivatives in muscle. Only Maia et al (2012b) identified low quantities of ricinoleic acid in muscle of goat kids fed diets supplemented with 3% of castor oil. More scarce are the studies on the effects of castor oil on milk FA composition.…”
Section: Introductionmentioning
confidence: 99%
“…Castor oil is unique due to a very high proportion of ricinoleic acid (12-OH,c9-18:1) and is usually considered as nonedible (Severino et al, 2012). Nevertheless, Brazilian research have demonstrated that castor oil can be incorporated in the diet of small ruminants without any deleterious effects on digestion (Maia et al, 2012a), growth (Maia et al, 2012b), and milk production (Queiroga et al, 2010). Moreover, castor oil is less prone to oxidative degradation than other vegetable oil ensuring longer conservation in tropical farm conditions (Medeiros et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%